The Study of the Concentration of Heavy Metals (As, Cd, Cr, Hg, Ni and Pb) in the Sediment of Coastal Area Receiving Effluent from Phetchaburi Municipal Wastewater Treatment System: The Royally LERD Project, Phetchaburi Province - Khowhit, Sateinpong; Chunkao, Kasem; Inkapatanakul, Wasin; Phewnil, Onanong; Boutson, Anukorn (วารสารพิษวิทยาไทย, 2020)
The aim of this study was to evaluated the concentrations of heavy metals (As, Cd, Cr, Hg, Ni and Pb) in the sediment of coastal areas receiving effluent from Phetchaburi municipal wastewater treatment system. The project focused on treating the municipal wastewater of Phetchaburi town municipality, with the use of simple technology and the introduction of the nature-by-nature process. After the treated municipal wastewater was released into the sea, the samples of the sediment were collected from the sea bed at a depth of 0-15 cm. in August 2012 (rainy season) and March 2013 (summer). The results were compared to the standard value of the sediment qualities coastal areas that were un-treated. It was found that the averages of arsenic (As), cadmium (Cd), chromium (Cr), mercury (Hg), nickel (Ni) and lead (Pb) at the sediment of coastal area in the Royal LERD project were 3.280, 0.023, 10.454, 0.015 2.963 and 18.831 mg/kg dry weight, respectively. These levels were in line and accepted with the standard qualities.